Strengthening the chemistry portion of the grade five elementary science currciculum at the U.P. Elementary School; a seminar paper - Soriano, Beatriz Aglibut 1925- ([Quezon City s.n.], 1965)
This paper determines chemistry concepts that can be added to strengthen the chemistry portion of the Grade V Elementary Science Curriculum at the UP Elementary School. These are the basic concepts on kinds, states, and changes in matter, composition of common substances, chemical action, chemical tests and applied chemistry.
Thesis (M.A.T.)--University of the Philippines
Keywords: Chemistry -- Study and teaching